SOSIALISASI TEKNIS DAN PENINGKATAN PEMELIHARAAN KELAPA SAWIT PADA WILAYAH PETANI SAWIT RAKYAT KELURAHAN NAMU UKUR SELATAN - Maisarah, Maisarah; Dian, Rahmad; Ginting, Makhrani Sari; Siregar, Ratu Mutiara; Barus, Friska Anggraini; Aznur, Tifany Zia (Penerbit Widina, Widina Media Utama, 2024)
The oil palm commodity is a source of income for most farming households, especially in the North Sumatra area. Namu Ukur Selatan Subdistrict is one of the subdistricts in Sei Bingai subdistrict, Langkat Regency, North Sumatra Province, Indonesia, which is one of the locations for oil palm planting centers. Palm oil is one of the main commodities planted by people in the region. A common problem faced by oil palm farmers in the region is a lack of information regarding the technical aspects of good oil palm plant maintenance and management. The aim of this activity is to increase the knowledge of oil palm farmers regarding oil palm cultivation practices, in addition to that, oil palm farmers in smallholder plantations receive information regarding aspects that influence the growth and productivity of oil palm. This service activity can also increase the production and productivity of independent farmers' palm oil, so that in the future the economic income of oil palm farmers can increase. The solution that can be provided is in the form of counseling, outreach and education related to good technical maintenance and cultivation of oil palm plants in accordance with the rules of good agricultural practices (GAP). This community service activity was carried out in Namu Ukur Selatan Village, Sei Bingai District for ± 30 days, consisting of preparation, socialization and education stages as well as carrying out activities by students and lecturers of the Institut Teknologi Sawit Indonesia (ITSI). The activity was attended by 20 people who are members of the People's Palm Oil Farmers, urban village heads, neighborhood chief, sub-district officials, local residents, lecturers from ITSI and supported by ITSI students. It is hoped that this community service activity will be able to educate the community on correct oil palm maintenance techniques and that the community can apply them to smallholder oil palm plantation.ABSTRAKKomoditi kelapa sawit menjadi sumber pendapatan bagi sebagian besar rumah tangga petani, terutama di daerah Sumatera utara. Kelurahan Namu Ukur Selatan merupakan salah satu kelurahan yang ada di kecamatan Sei Bingai, Kabupaten Langkat, Provinsi Sumatera Utara, Indonesia yang merupakan salah satu lokasi sentra pertanaman kelapa sawit. Sawit menjadi salah satu komoditi utama yang ditanam masyarakat di wilayah tersebut. Permasalahan umum yang dihadapi oleh petani sawit di wilayah tersebut adalah kurangnya informasi mengenai teknis pemeliharaan tanaman kelapa sawit yang baik dan pengelolaannya. Tujuan dari kegiatan ini dapat meningkatkan pengetahuan petani kelapa sawit terkait praktek budidaya tanaman kelapa sawit, selain itu petani kelapa sawit pada perkebunan rakyat mendapatkan informasi mengenai aspek-aspek yang mempengaruhi pertumbuhan dan produktivitas kelapa sawit. Kegiatan pengabdian ini juga dapat meningkatkan produksi dan produktivitas kelapa sawit petani mandiri, sehingga kedepannya pendapatan ekonomi petani kelapa sawit dapat meningkat. Solusi yang dapat diberikan yaitu berupa penyuluhan, sosialisasi dan edukasi terkait teknis pemeliharaan dan budidaya tanaman kelapa sawit yang baik yang sesuai dengan kaidah good agricultural practices (GAP). Kegiatan pengabdian masyarakat ini dilaksanakan di Kelurahan Namu Ukur Selatan, Kecamatan Sei Bingai selama ±30 hari yang terdiri dari tahap persiapan, sosialisasi dan edukasi serta pelaksanaan kegiatan oleh mahasiswa serta dosen Institut Teknologi Sawit Indonesia (ITSI). Kegiatan dihadiri oleh 20 orang yang tergabung dalam Petani Sawit Rakyat, lurah, kepling, perangkat kecamatan, warga setempat, dosen dari ITSI serta didukung oleh mahasiswa ITSI. Kegiatan pengabdian masyarakat ini diharapkan mampu mengedukasi masyarakat dalam teknis pemeliharaan kelapa sawit yang benar dan masyarakat bisa mengaplikasikan di perkebunan sawit rakyat.